Isorhamnetin attenuates renal interstitial fibrosis by targeting TWEAK/Fn14-mediated epithelial–mesenchymal transition - Chen, Yaping; Luo, Wenchuan; Guan, Hongxiang; Chen, Zixin; Chen, Zhihui; Xiao, Lijuan; Xu, Wen; Huang, Mei; Lin, Ya; Zhang, Yuqin; Peng, Weihua; Nan, Lihong (Frontiers in Immunology, 2025)
IntroductionIsorhamnetin (ISO), a prominent active compound found in the fruits of Hippophae rhamnoides L., exhibits various pharmacological activities. Recent studies have demonstrated that ISO possesses a significant renoprotective effect. Nevertheless, the specific targets and mechanisms through which ISO exerts its effects against renal interstitial fibrosis (RIF) remain insufficiently explored. The aims of this study were to explore the protective effects of ISO regulating epithelial–mesenchymal transition (EMT) and relieving RIF and to elucidate the underlying molecular mechanisms involved in the tumor necrosis factor-like weak inducer of apoptosis (TWEAK)/fibroblast growth factor-inducible molecule 14 (Fn14) pathway.MethodsWe explored the potential effects and mechanisms of ISO on RIF by using an in vitro EMT model of a transforming growth factor-β (TGF-β)-induced human proximal tubular cell line (HK-2) and an in vivo unilateral ureteral obstruction (UUO) model. The potential mechanism of the TWEAK/Fn14 pathway involving the protective action of ISO on renal tubules was explored by surface plasmon resonance (SPR) analysis and Fn14 overexpression on UUO rats.ResultsOur findings reveal that ISO can enhance cell morphology and effectively inhibit the migration ability of TGF-β-induced HK-2 cells. ISO also improved renal dysfunction and reduced tubular damage induced by UUO, significantly increasing E-cadherin expression and decreasing α-smooth muscle actin (α-SMA) and the main component of the ECM [type III collagen (Col III) and fibronectin (FN)] in vivo. The results show that ISO demonstrates potent inhibition of EMT in renal tubular epithelial cells, both in vivo and in vitro. The specific interaction between ISO and Fn14 was confirmed by SPR analysis. Overexpression of Fn14 counteracts the renoprotective effects of ISO, mitigating its influence on the inactivation of the TWEAK/Fn14 signaling pathway.ConclusionsThese confirmed that ISO inhibits the EMT of renal tubular epithelial cells by suppressing the TWEAK/Fn14 signaling pathway.